Oxidation of α-amino acids promoted by the phthalimide N-oxyl radical: A kinetic and product study. Issue 26 (28th June 2019) - Ticconi, Barbara; Mazzonna, Marco; Lanzalunga, Osvaldo; Lapi, Andrea
Abstract: A kinetic study of the hydrogen atom transfer (HAT) reaction from a series of N -Boc- or N -Acetyl-protected amino acids to the phthalimide N -oxyl radical (PINO) was carried out to obtain information about reactivity and selectivity patterns. With amino acids containing aliphatic side chains, the 2nd order rate constants are of the same order of magnitude, in agreement with a HAT process involving the Cα−H bond. Proline is the most reactive substrate suggesting that HAT process involves the Cδ −H bond instead of Cα −H bond. These results are confirmed by the product analysis of the aerobic oxidations of the corresponding N -Boc and N -Ac protected amino acids methyl esters promoted by N -hydroxyphthalimide. Comparison of our results with those reported for HAT reactions to other radical species indicates that PINO displays electrophilic characteristics that are intermediate between those observed for the more stable Br radical and the more reactive cumyloxyl radical. Graphical abstract: Image 1